Investigating patterns of donor and recipient sports of talent transfer paralympians - Green, A.; Mulcahy, R.; Fleischman, D.; MacDonald, L.; Kean, B. (Adapted Physical Activity Quarterly, 2024)
Talent transfer has enabled elite athletes to be successful in another sport, with great potential in para-sport. Previous research suggests that similarities between donor and recipient sports may facilitate talent transfer; however, this remains unclear in para-sport. This study investigated patterns between donor and recipient sports` characteristics, identifying the impact on talent transfer in para-sport. An Australian case study utilizing secondary data of 38 Australian Paralympians who competed at the Paralympic Games from 2000 through 2020 was analyzed. Results demonstrated that similarities between sports were not significantly associated with successful talent transfers between Paralympic sports. Understanding patterns associated with successful Paralympic talent transfers offers a foundation of knowledge for designing and developing future talent-transfer pathways and research. Based on this study, it is recommended that sport administrators and practitioners explore greater opportunity for talent transfer in para-sport, rather than limiting talent-transfer opportunities based on athletes` donor sports.